Photo catalytic oxidation technology for desalination pretreatment - Liu, Dan. (2008)
The aim of this study was to design, fabricate and set up a new ultraviolet PCO reactor system with suspended TiO2 catalyst for destroying the oil contaminants in local saline water prior to desalination process.